2021
DOI: 10.1097/opx.0000000000001688
|View full text |Cite
|
Sign up to set email alerts
|

2017 National Optometry Workforce Survey

Abstract: Planning for the effective delivery of eye care, on all levels, depends on an accurate and detailed knowledge of the optometric workforce and an understanding of demographic/behavioral trends to meet future needs of the public. PURPOSE:The purposes of this study were to assess the current and future supply of doctors of optometry and to examine in-depth trends related to (1) demographic shifts, (2) sex-based differences, (3) differences in practice behaviors in between self-employed and employed optometrists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The number of respondents was high and represented a significant population of eye care practitioners who are involved in orthokeratology. In comparison, a scientific study from 2017 data published in 2021 sent surveys to 4050 randomly sampled optometrists from a population of 45,033 listed in the American Optometric Association's Optometry Master Data File database 33 . They received a total of 1158 responses that represented 2.6% of the total number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of respondents was high and represented a significant population of eye care practitioners who are involved in orthokeratology. In comparison, a scientific study from 2017 data published in 2021 sent surveys to 4050 randomly sampled optometrists from a population of 45,033 listed in the American Optometric Association's Optometry Master Data File database 33 . They received a total of 1158 responses that represented 2.6% of the total number.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a scientific study from 2017 data published in 2021 sent surveys to 4050 randomly sampled optometrists from a population of 45,033 listed in the American Optometric Association's Optometry Master Data File database. 33 They received a total of 1158 responses that represented 2.6% of the total number. In addition, a scientific study on surveys showed that the sample size estimation to result in valid findings for a population of 3000 is 249.…”
Section: Discussionmentioning
confidence: 99%
“…While some professions are evolving to assume more gender-balanced positioning (Anliak & Beyazkurk, 2008 ; Heath et al, 2021 ), the early education and care sector continues to be predominately comprised of women (Peeters et al, 2015 ; Reich-Shapiro et al, 2020 ). Former research has sought to unmask institutional and societal barriers faced by female ECECs, typically in linkage to working in a profession that is care-rooted (Halfon & Langford, 2015 ; Moss, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent optometric workforce survey, 33 we assumed that a full‐time equivalent (FTE) eye care clinician (optometrist or ophthalmologist) examines 60 patients per week and takes 5 weeks of annual leave (minimum entitled annual leave is 4 weeks in the UK and Ireland). The numbers of optometrists and ophthalmologists registered in the UK and Ireland between 2015–2020 were obtained from professional registration councils (CORU, Medical Council of Ireland, General Optical Council, General Medical Council) through annual reports or freedom of information requests.…”
Section: Methodsmentioning
confidence: 99%